Effect of seminal plasma and sperm of boars valued by freezability on seminal cryopreservation (2016)
The aim of this study was to determine the effect of sperm and seminal plasma (SP) on the freezability of porcine semen. Semen of eight commercial males from two farms in the central-western region of Colombia (four boars in each farm) was frozen and tested to select two males with high freezability (MHF) and two with low freezability (MLF), according to the percentage of functionally competent sperm (FCS). Immediately after the collection was completed, the SP and sperm from the males selected were separated by centrifugation to combine the two types of plasma with the two types of sperm, incubate them for three hours and then freeze them. The variables evaluated were: sperm morphology, structural and functional integrity of plasmatic membrane, progressive and total motility, DNA fragmentation, acrosome integrity, capacitated sperm and FCS. The combination of sperm and plasma of MHF recorded the highest value (P0.01) of acrosome integrity (24.3 ± 0.082 vs 6.076 ± 0.16) when compared to MLF plasma and cells. Membrane structural integrity was higher (P0.01) with MHF (53.56 ± 0.0395) than with MLF plasma (47.49 ± 0.0419). The differences in porcine semen freezability depend on interactions between seminal plasma and sperm.